2020
DOI: 10.1038/s41586-020-2598-9
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-reactive T cells in healthy donors and patients with COVID-19

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

121
1,297
7
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,237 publications
(1,438 citation statements)
references
References 37 publications
121
1,297
7
13
Order By: Relevance
“…Interestingly, the SARS-CoV-2-responsive CD4 + T cells from unexposed donors also responded to similar epitopes present in endemic coronaviruses 229E and OC43 36 . Therefore, cross-reactive T cells might be the base for this cellular activation in the absence of humoral responses, although the dynamics of this cross-reactivity is not understood yet.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, the SARS-CoV-2-responsive CD4 + T cells from unexposed donors also responded to similar epitopes present in endemic coronaviruses 229E and OC43 36 . Therefore, cross-reactive T cells might be the base for this cellular activation in the absence of humoral responses, although the dynamics of this cross-reactivity is not understood yet.…”
Section: Discussionmentioning
confidence: 87%
“…It has been described the generation of immunogenic CD4 + and CD8 + responses against SARS-CoV-2 antigens that correlate with the presence of speci c antibodies against the virus 34,35 . However, up to 35% of unexposed donors (without detectable anti-SARS-CoV-2 speci c antibodies) showed SARS-CoV-2reactive CD4 + T cells, while 83% of antibody-bearing patients displayed comparable cellular responses 36 .…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, previous studies suggested the potential role of pre-existing immunity in fighting COVID-19 [6,23,24]. Therefore, the predicted MHC-II T cell promiscuous epitopes of the SARS-CoV-2 S protein were compared to those from the other six HCoVs.…”
Section: Resultsmentioning
confidence: 99%
“…The cryo-EM structure of the S protein [20] and the neutralizing antibodies binding to the S protein [21,22] were determined. Besides neutralizing antibodies, studies have also shown the importance of CD4 T cell response in the control of SARS-CoV-2 infection and possible preexisting immunity in healthy individuals without exposure to SARS-CoV-2 [6,23,24]. Overall, successful vaccination is likely linked to a robust and long-term humoral response to the SARS-CoV-2 S protein, which could be further enhanced by the rational structural design of the protein.…”
Section: Covid-19 Vaccines Currently In Clinical Trials Including Othmentioning
confidence: 99%
“…cytokines) 11 . The innate immune system seems to be insu cient to rapidly clear SARS-CoV-2 infection by itself, as SARS-CoV-2-speci c T and B cell responses develop in most patients [12][13][14] . Virus-speci c T cell responses and neutralizing antibodies, typically generated in a T cell dependent manner, are considered essential for viral clearance 15 .…”
Section: Introductionmentioning
confidence: 99%